The role of Islamic banks to attract savings to funding banking activities in Iraq For period (2008-2012) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Islamic banks are a financial institution that is interested in attracting financial savings from financial entities and directing them towards those with financial deficits, both for consumption purposes or for investment purposes. It provides banking services provided by commercial banks and other services But based on the principles and principles of Islamic law, and because of its recent emergence in Iraq, its ability to attract savings is not like non-Islamic commercial banks, which puts them in the option of using their capital to achieve its objective of banking. The research started from the premise that "Islamic banks in Iraq during the period (2008-2012) rely on their capital to perform their activities more than they rely on deposits of all kinds." The research sought to prove the existence of the research problem and its hypothesis by using descriptive and quantitative historical analysis and relying on the aggregate data provided by the CBI's publications and the general budgets of the Islamic and commercial banks in general. The most important conclusions of the research: the validity of the hypothesis of research, and the Islamic banks in Iraq has grown all of the funds and their capital in an encouraging manner, despite the recent experience.